Site-directed Mutagenesis Switching a Dimethylallyl Tryptophan Synthase to a Specific Tyrosine C3-Prenylating Enzyme - Fan, Aili; Zocher, Georg; Stec, Edyta; Stehle, Thilo; Li, Shu-Ming (The Journal of biological chemistry, 2015)
The tryptophan prenyltransferases FgaPT2 and 7-DMATS (7-dimethylallyl tryptophan synthase) from Aspergillus fumigatus catalyze C4- and C7-prenylation of the indole ring, respectively. 7-DMATS was found to accept l-tyrosine as substrate as well and converted it to an O-prenylated derivative. An acceptance of l-tyrosine by FgaPT2 was also observed in this study. Interestingly, isolation and structure elucidation revealed the identification of a C3-prenylated l-tyrosine as enzyme product. Molecular modeling and site-directed mutagenesis led to creation of a mutant FgaPT2_K174F, which showed much higher specificity toward l-tyrosine than l-tryptophan. Its catalytic efficiency toward l-tyrosine was found to be 4.9-fold in comparison with that of non-mutated FgaPT2, whereas the activity toward l-tryptophan was less than 0.4% of that of the wild-type. To the best of our knowledge, this is the first report on an enzymatic C-prenylation of l-tyrosine as free amino acid and altering the substrate preference of a prenyltransferase by mutagenesis.Dimethylallyl tryptophan synthase FgaPT2 catalyzes in nature the C4-prenylation of indole ring. FgaPT2 also catalyzes in vitro a regular C3-prenylation of l-tyrosine; its mutant FgaPT2_K174F showed a much higher catalytic activity toward l-tyrosine than l-tryptophan. Single mutation on the key amino acid switches the tryptophan C4-prenyltransferase to a tyrosine C3-prenylating enzyme. The first l-tyrosine C3-prenylating enzyme was created by molecular modeling-guided mutagenesis.